2020
DOI: 10.1016/j.nedt.2020.104404
|View full text |Cite
|
Sign up to set email alerts
|

Memento Mori: Can art assist student nurses to explore death and dying? A qualitative study

Abstract: Link to publication on Research at Birmingham portal General rightsUnless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law.• Users may freely distribute the URL that is used to identify this publication.• Users may download and/or print one copy of the publication from the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Lippe and Becker ( 2015 ) describe the positive impact that running simulations on the withdrawal of care had on students' attitudes and perceived competence in caring for a dying patient. Similarly, Hançer Tok and Cerit ( 2021 ) identified that implementing creative drama workshops focussed on death and dying patients and reflection on artworks (Nicol & Pocock, 2020 ) positively impacted student learning and students' attitudes towards caring for dying patients indicating perhaps the need for more creative approaches to learning. The literature suggests innovative educational practices alongside supported clinical experience will offer students the best opportunity to feel comfortable and actively participate in the end‐of‐life care.…”
Section: Discussionmentioning
confidence: 99%
“…Lippe and Becker ( 2015 ) describe the positive impact that running simulations on the withdrawal of care had on students' attitudes and perceived competence in caring for a dying patient. Similarly, Hançer Tok and Cerit ( 2021 ) identified that implementing creative drama workshops focussed on death and dying patients and reflection on artworks (Nicol & Pocock, 2020 ) positively impacted student learning and students' attitudes towards caring for dying patients indicating perhaps the need for more creative approaches to learning. The literature suggests innovative educational practices alongside supported clinical experience will offer students the best opportunity to feel comfortable and actively participate in the end‐of‐life care.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that this idea must link to the central strategic question of how to disconnect the direct image of "death" with "palliative care". The simple fact of creating an open environment that promotes discussion of the subject among people, using art, and fostering strategies such as active listening and education for intercultural sensitivity, can help to develop awareness about death based on values like trust, instead of fear (Nicol & Pocock, 2020;Rojí et al, 2017). A systematic review of PC education has recommended teaching as authentically as possible the patient's experience of receiving that care.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 El profesional de enfermería debe mostrar sus cualidades intra e interpersonales para el cuidado humanizado, evidente en expresiones faciales, miradas, comentarios, sonrisas y otras pequeñas acciones. [37][38][39][40] Tema 3: factores que impiden dignificar el proceso de fin de vida La actitud de indiferencia de algunos profesionales y estudiantes, sumados al sentimiento de lástima hacia los pacientes, al duelo no gestionado de manera oportuna y la falta de conocimientos teóricos y prácticos, son factores que no permiten la muerte digna. 35,36 En muchas ocasiones, esto se asocia con aspectos psicoemocionales, debido a la gran carga laboral y los altos niveles de estrés y agotamiento [35][36][37][38] , que llevan a abstenerse de brindar cuidados, comunicar o establecer relaciones cercanas con pacientes en etapa terminal, mostrando desinterés y falta de comunicación e información sobre su condición, que genera sentimientos de negación, miedo y ansiedad.…”
Section: Tema 1: Dignidad Humanaunclassified
“…La formación integral incluye los cuidados paliativos para aliviar el dolor y el sufrimiento, así como mejorar la calidad de vida de las personas y familiares que se enfrentan a una enfermedad potencialmente mortal. Así mismo, son relevantes los aspectos psicosociales y espirituales frente a los cuales la tanatología ofrece orientaciones para la práctica de enfermería 33,35,39,40 , integradas con los modelos como la Teoría del Final Tranquilo de la Vida (Ruland y Moore) y la Teoría del Cuidado Humano (Watson). 10,11 b) Fortalecimiento de habilidades sociales y trato humanizado: el cuidado se expresa en múltiples actos que requieren empatía y compasión para generar relaciones terapéuticas, teniendo en cuenta el sistema de apoyo y el contexto.…”
Section: Tema 1: Dignidad Humanaunclassified
See 1 more Smart Citation